Plant-derived pyrrolizidine alkaloid protects eggs of a moth (Utetheisa ornatrix) against a parasitoid wasp (Trichogramma ostriniae) - Bezzerides, Alexander (National Academy of Sciences, 2004)
Pyrrolizidine alkaloid (PA), sequestered by the moth Utetheisa ornatrix from its larval food plant, is transmitted by both males and females to the eggs. Males confer PA on the female by seminal infusion, and females pass this gift, together with PA that they themselves procured as larvae, to the eggs. Here we show that PA protects the eggs against parasitization by the chalcidoid wasp, Trichogramma ostriniae. Eggs laid subsequent to a first mating of an Utetheisa female receive most of their PA from the female. The amount they receive from the male is insufficient to provide for full protection. However, female Utetheisa are promiscuous and therefore likely to receive PA on a cumulative basis from their male partners.